Identification of a Hypervirulent Pathotype of Rice yellow mottle virus: A Threat to Genetic Resistance Deployment in West-Central Africa - Hébrard, E.; Pinel Galzi, A.; Oludare, A.; Poulicard, N.; Aribi, J.; Fabre, S.; Issaka, S.; Mariac, C.; Dereeper, A.; Albar, L.; Silué, D.; Fargette, D. (Scientific Societies, 2018)
Rice yellow mottle virus (RYMV) causes high losses to rice production in Africa. Several sources of varietal high resistance are available but the emergence of virulent pathotypes that are able to overcome one or two resistance alleles can sometimes occur. Both resistance spectra and viral adaptability have to be taken into account to develop sustainable rice breeding strategies against RYMV. In this study, we extended previous resistance spectrum analyses by testing the rymv1-4 and rymv1-5 alleles that are carried by the rice accessions Tog5438 and Tog5674, respectively, against isolates that are representative of RYMV genetic and pathogenic diversity. Our study revealed a hypervirulent pathotype, named thereafter pathotype T′, that is able to overcome all known sources of high resistance. This pathotype, which is spatially localized in West-Central Africa, appears to be more abundant than previously suspected. To better understand the adaptive processes of pathotype T′, molecular determinants of resistance breakdown were identified via Sanger sequencing and validated through directed mutagenesis of an infectious clone. These analyses confirmed the key role of convergent nonsynonymous substitutions in the central part of the viral genome-linked protein to overcome RYMV1-mediated resistance. In addition, deep-sequencing analyses revealed that resistance breakdown does not always coincide with fixed mutations. Actually, virulence mutations that are present in a small proportion of the virus population can be sufficient for resistance breakdown. Considering the spatial distribution of RYMV strains in Africa and their ability to overcome the RYMV resistance genes and alleles, we established a resistance-breaking risk map to optimize strategies for the deployment of sustainable and resistant rice lines in Africa.